The New Woman as Satirist or Butt of Satire. (2nd January 2017) - Boa, Elizabeth
Abstract : The New Woman in the work of Mascha Kaléko, Hannah Höch, and Irmgard Keun appears both as the satirist attacking the misogyny of a superseded patriarchy and as the butt of satire as a puppet of modern market forces; in Thea von Harbou's Metropolis she comes in two versions as harbinger of chaos or motherly saviour of the people. Kaléko's poem, Höch's photomontages and Harbou's novel all exhibit a characteristic shift in Weimar satire from an animalistic to a mechanistic mode of dehumanization. Read in sequence, Keun's three novels of the 1930s convey how the growing political threat of National Socialism came to overshadow the social and economic struggles of young women looking for new freedoms.